Optimizing tissue-specific antisense oligonucleotide-peptide conjugates. - Betts, C; Hammond, S; Yin, H; Wood, M (2012)
Cell-targeting peptides which improve tissue-specific delivery of antisense oligonucleotides (AONs) are a new exciting "next-generation" potential AON therapy. New peptides are regularly developed which increase targeting and cell penetration for the AON treatment of mRNA misregulated diseases. Optimization of these peptide conjugate AONs requires systematic treatment and methods of analysis. This chapter describes methods for analyzing cell-targeting peptide conjugated AONs in primary cultured cell lines and for local and systemic delivery to the mouse for the treatment of Duchenne muscular dystrophy (DMD). Chimeric and novel cell-penetrating peptides have already been described to induce high levels of exon skipping and dystrophin protein expression in tissues body-wide at very low doses of AON. Screening of future novel peptides may be achieved by preliminary in vitro screening followed by in vivo administration of the most promising peptide-conjugated AONs. Physiological and functional correction of dystrophin protein may be confirmed by a number of techniques as described and allows for the fast-tracking of candidate peptides to drug trial for DMD.